2016
DOI: 10.1002/acp.3295
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Initial Pleasantness for Fading Affect, Fixed Affect, Flourishing Affect, and Flexible Affect Events

Abstract: Over time, autobiographical memories demonstrate fixed affect (i.e., maintain initial affect), fading affect, flourishing affect (i.e., increased affect), or flexible affect (i.e., change from unpleasant to pleasant or vice versa). Walker and Skowronski argued that events low in initial pleasantness are more likely to exhibit flourishing affect and flexible affect and that unpleasant events are more likely to demonstrate flexible affect than pleasant events. However, because of the low frequency of flourishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The 2,362 additional events that changed affect in an "unusual" way were removed from the remaining 13,591 (15.634%) events, leaving 11,229 "pure" events. This loss of events was reasonable based on Gibbons and Rollins [84] who showed that 15.32% of their events across four experiments indicated "unusual" fading affect in the form of flourishing (increased) and flexible (changed to the other valence) affect. We also calculated event intensity for pleasant and unpleasant events by calculating the absolute value of the initial affect rating.…”
Section: Materials Procedures Measures Design and Analysessupporting
confidence: 60%
See 1 more Smart Citation
“…The 2,362 additional events that changed affect in an "unusual" way were removed from the remaining 13,591 (15.634%) events, leaving 11,229 "pure" events. This loss of events was reasonable based on Gibbons and Rollins [84] who showed that 15.32% of their events across four experiments indicated "unusual" fading affect in the form of flourishing (increased) and flexible (changed to the other valence) affect. We also calculated event intensity for pleasant and unpleasant events by calculating the absolute value of the initial affect rating.…”
Section: Materials Procedures Measures Design and Analysessupporting
confidence: 60%
“…The data for the presidential election study came from four events (pleasant and unpleasant non-political events as well as the 2016 Presidential election [84] event and a comparably, but opposite, emotionally intense event) provided by 310 participants [85]. The data from the relationship study came from 12 events (3 pleasant and 3 unpleasant relationship events as well as 3 pleasant and 3 unpleasant non-relationship events) provided by 239 participants from the relationship study [86].…”
Section: Participantsmentioning
confidence: 99%
“…On the one hand, this may reduce (experimental) control. On the other hand, online surveys provide an anonymous setting that may reduce social desirability and make it easier to describe personal memories (Gibbons & Rollins, 2016). Fourth, we only tested for linear effects of intensity, time since event, and SCC.…”
Section: Limitationsmentioning
confidence: 99%
“…However, existing evidence suggests that this is not the case. For example, T. Ritchie et al (2009) and Gibbons and Rollins (2016) showed emotions related to positive events were rated at the occurrence as more extreme than those associated with negative events, thus the locus of change producing FAB sits with affect ratings regarding how pleasant/unpleasant the events are in the current moment (i.e., at retrieval) rather than the retrospective recollection of the affect felt at the time the events occurred. Even though the evidence indicates that positive and negative event extremity at the time of the event does not account for FAB, there is always the possibility that such extremity differences are related to age.…”
Section: Discussionmentioning
confidence: 99%